Satlantas Efforts in Preventing Traffic Accidents in the Legal Territory of the Buleleng Police - Ketut Reni Juliani (Indonesian Journal of Police Studies, 2021)
The large number of vehicles in Buleleng Regency has an impact on the traffic situation and conditions in Buleleng Regency. Various kinds of problems that occur include congestion, traffic violations, and traffic accidents. To minimize the occurrence of traffic accidents, the participation of related parties, especially the police through the Traffic Unit, is required.The researcher uses management theory, SWOT analysis theory, crime prevention theory, and the concept of traffic accidents as an analytical knife. The research approach used is a qualitative approach with the type of research in the form of field research. The technique of collecting data is through interviews, observations, and document studies which are then analyzed by data reduction, data presentation, and drawing conclusions. The research was carried out at the Buleleng Police Station, the findings obtained by the researchers can be concluded that traffic accidents in Buleleng Regency for the 2016-2020 period experienced fluctuations and were dominantly caused by human factors, vehicle factors, road factors, and weather/natural factors with the dominant being caused by human factors. Satlantas efforts in preventing traffic accidents are manifested in several efforts, namely: preemptive efforts, socializing traffic rules and utilizing social media; preventive efforts by making banners calling for orderly traffic at traffic accident-prone points and patrolling at traffic accident-prone points; repressive efforts by carrying out motor vehicle raids together with relevant agencies. The research also found various obstacles faced by the Buleleng Police Traffic Unit, including the lack of adequate internal and external facilities and infrastructure, the lack of budgetary direction, and the low awareness of the orderly traffic of road users in Buleleng Regency. From these findings, the researcher gave recommendations to the leadership of the Buleleng Police to provide supporting internal and external infrastructure, design a more targeted budget, and further intensify coordination with related agencies in terms of adding road infrastructure.